Competence in Sports Pharmacy among Pharmacy Students in Norway - Natalia Dabrowska; Lone Malmberg; Hadis Nejati; Cecilie Bach Volle; Maren Røssing Witzø; Hatice Yaman; Parisa Gazerani (MDPI AG, 2023)
Pharmacists are competent to promote the proper use of medicines. According to the International Pharmaceutical Federation, pharmacists must develop competence in sports pharmacy and the contents of the World Anti-Doping Agency code. This explorative study aimed to identify the status of sports pharmacy in pharmacy education in Norway and competence in sports pharmacy among Norwegian pharmacy students. The study curricula of pharmacy education were examined for the content of sports pharmacy. An online questionnaire was also developed and distributed among pharmacy students. The anonymous survey collected demographic information and data on competence in sports pharmacy. Data from 122 participants were analyzed. Only 22.5% of pharmacy students had acquired a form of training in sports pharmacy and 91.7% wished to gain higher competence. In total, 40.2% of respondents were uncomfortable in advising athletes and trainers on medication use in sports. Study year was found to correlate with competence level with a significant difference between the 3rd year (bachelor) and 5th year (master) students. Age, institution, and number of years engaged in sports were not associated with competence level. The inclusion of sports pharmacy in pharmacy programs holds practical relevance for enhancing competency levels. This implementation can be realized through the integration of sports pharmacy modules and/or the incorporation of research-based activities.